The effect of corporate social responsibility disclosure, sales growth, and leverage on financial performance - Aulia, Ika Rahma; Saebani, Akhmad (Jurnalku, 2026)
This research is a quantitative study which aims to examine the effect of corporate social responsibility disclosure, sales growth, and leverage, on financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. The background of this study is based on the importance of financial performance as an indicator of a company's success in managing resources, as well as the increasing attention to social responsibility practices and corporate funding policies. The research uses secondary data obtained through annual reports and sustainability reports from the manufacturing sector which are listed on the Indonesia Stock Exchange (IDX) in 2022-2024. The sampling criteria were selected using a purposive sampling method, resulting in 34 companies with 102 observational data points as research objects. Hypothesis testing in this study uses a panel data regression model. The research model is processed and tested using STATA 12. The results of this study are corporate social responsibility disclosure had no effect on financial performance, this finding indicates that CSR disclosure has not been able to directly increase the profitability of manufacturing companies during the observation period.  Sales growth had a significant positive effect on financial performance, indicating that increasing revenue from operational activities is a major factor in improving company profitability.Leverage had a significant negative effect on financial performance, indicating that high debt usage can increase interest expenses and financial risks, thereby suppressing company profits.